Effect of Local Estrogen on Repairing Tympanic Membrane Perforation - Behrouz Barati; Golfam Mehrparvar; Matin Ghazizadeh (Iranian Journal of Otorhinolaryngology, 2020)
Introduction: Tympanoplasty is a surgical treatment of tympanic membrane perforation. Many efforts have been made to increase the success rate of tympanoplasty. Some studies confirmed the positive role of estrogen in wound healing. The current study was conducted to evaluate the effect of topical estrogen on the success rate of tympanoplasty.   Materials and Methods: A total of 85 patients were randomly assigned to the case and control groups. Otomicroscopic examination was performed before and 3 months following the operation. At the final stage of tympanoplasty, gelfoam was placed on the lateral side of the graft. It was soaked in dexamethasone in the control group and combination of dexamethasone and estradiol valerate solution in the case group. Hearing thresholds were measured by audiometric tests pre- and postoperatively. Hearing levels were assessed as the mean air conduction (AC) at 500, 1000, and 2000 Hz. The graft status was evaluated using otomicroscopic examination 3 months following the operation.   Results: Otomicroscopic examination revealed successful graft healing in 23 of 37 and 29 of 36 patients in the control and case groups, respectively. A higher rate (80.55%) of graft repair was observed in the estradiol group, compared to that (62.16%) reported for the control group; however, the difference was not statistically significant (P=0.08). The average improvement values of the AC levels were 20.45 and 24.7 dB in the control and case groups, respectively (P=0.3). Statistical analysis among the subgroup of patients with small perforations showed that the success rate of tympanoplasty was significantly higher in the estradiol group, compared to that reported for the control group (P=0.03).   Conclusion: Although topical estrogen was generally ineffective in increasing the success rate of tympanoplasty, it improved the success rate among patients with small tympanic membrane perforations.